2009
DOI: 10.1007/s00268-009-0288-8
|View full text |Cite
|
Sign up to set email alerts
|

Ratio Between Metastatic and Examined Lymph Nodes (N Ratio) May Have Low Clinical Utility in Gastric Cancer Patients Treated by Limited Lymphadenectomy: Results from a Single‐Center Experience of 526 Patients

Abstract: When a small number of lymph nodes are analyzed, the N ratio can discriminate patients better than TNM classification. However, because a small number of retrieved nodes produced only a small number of pNR1 patients, the N ratio classification cannot be justified for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 36 publications
3
20
0
Order By: Relevance
“…To evaluate the rN staging system, some previous reports excluded patients with fewer than 16 LNs retrieved [16,20,22]; some researchers preferred the patients treated by limited lymphadenectomy, [9,10,18,23]; and some centers evaluated the rN system as an independent prognostic factor in gastric cancer regardless of the type of lymphadenectomy, or in both [15 and B15 LNs examined [17,19,24,25], as we did in our report. All the reports indicated that the rN staging system has superiority in prognosis assessment compared with the traditional AJCC pN system.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…To evaluate the rN staging system, some previous reports excluded patients with fewer than 16 LNs retrieved [16,20,22]; some researchers preferred the patients treated by limited lymphadenectomy, [9,10,18,23]; and some centers evaluated the rN system as an independent prognostic factor in gastric cancer regardless of the type of lymphadenectomy, or in both [15 and B15 LNs examined [17,19,24,25], as we did in our report. All the reports indicated that the rN staging system has superiority in prognosis assessment compared with the traditional AJCC pN system.…”
Section: Discussionmentioning
confidence: 87%
“…The Cox multivariate analysis showed that rN has a prognostic value independent of the extent of lymphadenectomy. Many previous reports used Cox multivariate examinations, including both pN stage and rN stage, for proving the superiority of the LN ratio system [9,[15][16][17][18][19][20]. The pN and rN systems, two definitions of classifications for staging lymph node status, were highly correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the low number of patients with a low N-ratio we used a higher cut-off point. This can bias our results and give a seemingly higher prognostic value than the TNMclassification; some authors have questioned the clinical usefulness in case of low numbers of nodes [29]. In the new AJCC/UICC TNM classification ( …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 93%
“…For more accurate staging and a more reliable assessment of the prognosis, a new classification system was proposed, based on the ratio of the metastatic lymph nodes to the total number of lymph nodes (N ratio). The N ratio classification is advocated to avoid the stage migration phenomenon, and to be more effective in determining the prognosis, and thus it can be used in instead of the N clas sification [1,3,13,14,[16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%